A new index of flat breaststroke propulsion: A comparison of elite men and women - Seifert, L.; Chollet, D. (Journal of Sports Sciences, 2005)
This study examined arm and leg coordination and propulsion during the flat breaststroke in nine elite male and eight elite female swimmers over three race paces (200 m, 100 m and 50 m). Coordination was expressed using four temporal gaps (T1, T2, T3, T4), which described the continuity between the propulsive phases of the limbs, as recorded on a video device (50 Hz). Glide duration was denoted T1, the time between the beginning of arm and leg recovery was denoted T2, the time between the end of arm and the leg recovery was denoted T3, and the time between 90° of flexion during arm recovery and 90° during leg recovery was denoted T4. Using these temporal gaps, four stroke phases (propulsion, glide, recovery and leg insweep) could be followed over a complete arm and leg stroke. The total duration of arm and leg propulsion was assessed by a new index of flat breaststroke propulsion (IFBP). Velocity, stroke rate and stroke length were also calculated for each pace. The elite swimmers showed short T2, T3 and T4; moreover, T1 decreased when the pace increased. Expertise in the flat breaststroke was thus characterized by synchronized arm and leg recoveries and increased continuity in the arm and leg propulsions with increasing velocity. Differences between the sexes in the spatio-temporal parameters were possibly due to anthropometric differences (the men were heavier, older and taller than the women) and different motor organization linked to arm and leg coordination (shorter T3, body glide and body recovery, and greater body propulsion and higher IFBP in the men). The men's propulsive actions showed greater continuity, particularly in the sprint. The best men adopted a superposition coordination and thus had the ability to overcome very great active drag. Temporal gap measurement and the IFBP are practical indicators of arm and leg coordination and propulsion that can be exploited by coaches and swimmers to increase the continuity between propulsive actions during the flat breaststroke.